2014
DOI: 10.1007/s10863-014-9553-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex-I-ty in aging

Abstract: The role of mitochondrial complex I in aging has been studied in both C. elegans and Drosophila, where RNAi knock down of specific complex I subunits has been shown to extend lifespan. More recently, studies in Drosophila have shown that an increase in mitochondrial activity, including complex I-like activity, can also slow aging. In this review, we discuss this apparent paradox. Improved maintenance of mitochondrial activity, mitochondrial homeostasis, may be responsible for lifespan extension in both cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Similar lifespan extension was conferred by Ndx, the NDH2 from Ciona intestinalis (Gospodaryov et al, 2014). It was initially assumed that lifespan extension by NDH2 is due to a) a decrease in NADH/NAD + ratio (Stefanatos and Sanz, 2011;Scialò et al, 2013;Hur et al, 2014) or b) a decrease in ROS production by complex I (Scialò et al, 2013). It was recently shown that mitochondria of Ndi1p-expressing cells produced more ROS (Scialò et al, 2016).…”
Section: Ndh2 As a Tool To Study Ageingmentioning
confidence: 93%
“…Similar lifespan extension was conferred by Ndx, the NDH2 from Ciona intestinalis (Gospodaryov et al, 2014). It was initially assumed that lifespan extension by NDH2 is due to a) a decrease in NADH/NAD + ratio (Stefanatos and Sanz, 2011;Scialò et al, 2013;Hur et al, 2014) or b) a decrease in ROS production by complex I (Scialò et al, 2013). It was recently shown that mitochondria of Ndi1p-expressing cells produced more ROS (Scialò et al, 2016).…”
Section: Ndh2 As a Tool To Study Ageingmentioning
confidence: 93%
“…This may make PCD pathways particularly vulnerable to maladaptive signals during aging. Third, the important role of the mitochondria and ROS in PCD is likely a factor, because mitochondria appear to be particularly susceptible to damage and malfunction during aging across species (Bernhardt et al, 2014; Hur et al, 2014; Wallace, 2010). …”
Section: Why Is Pcd Mis-regulated During Aging?mentioning
confidence: 99%
“…In both Drosophila and C. elegans , RNAi inhibition of certain genes encoding ETC components can increase life span [7, 313315]. This result was initially interpreted to suggest that life span increase might be due to decreased metabolic activity.…”
Section: The Mitochondrial Stress Response and Unfolded Protein Respomentioning
confidence: 99%